Ginkgolide B ameliorates NLRP3 inflammasome activation after hypoxic-ischemic brain injury in the neonatal male rat. Issue 69 (October 2018) - Chen, Aiming; Xu, Yin; Yuan, Jun
Highlights: GB alleviated hypoxic-ischemic brain injury in the neonatal male rat. GB treatment dramatically suppressed microglia activation and NLRP3 expression. GB pretreatment significantly inhibited signal 1 and signal 2 of NLRP3 inflammasome activation. Abstract: Introduction: Perinatal hypoxic-ischemic (HI) insult is an important cause of brain injury in neonates. The development of novel treatment strategies for neonates with HI brain injury is urgently needed. Ginkgolide B (GB) is a main component of Ginkgo biloba extracts with a long history of use in traditional Chinese medicine. However, it is unknown whether GB could play a protective role in hypoxic stress in immature animals. Methods: Using neonatal hypoxic-ischemic (HI) brain injury model of rat pups, neurological score, infarct size, and brain edema were evaluated after HI injury. The activation of microglia and the production of IL-1β and IL-18 were detected by immunohistochemistry and ELISA, respectively. A priming signal (NF-κB P65) and an activation signal (Caspase-1) of NLRP3 inflammasome activation were detected by western blot analyses. Results: GB administrated 30 min prior to ischemia induction can improve neurological disorder, reduce infarct volume and alleviate cerebral edema. Compared with the HI groups, GB inhibited the activation of microglia and decreased the production of IL-1β and IL-18 in neocortex. Furthermore, GB reduced NLRP3 expression mainly in microglia, and significantly inhibited the expression of Caspase-1 and the nuclear translocation of NF-κB P65, preventing NLRP3 inflammasome activation. Conclusions: GB ameliorates hypoxic-ischemic brain injury in the neonatal male rat via inhibiting NLRP3 inflammasome activation.